Exendin-4 protects mitochondria from reactive oxygen species induced apoptosis in pancreatic Beta cells. - Zhen Li (Public Library of Science (PLoS), 2013)
Objective Mitochondrial oxidative stress is the basis for pancreatic β-cell apoptosis and a common pathway for numerous types of damage, including glucotoxicity and lipotoxicity. We cultivated mice pancreatic β-cell tumor Min6 cell lines in vitro and observed pancreatic β-cell apoptosis and changes in mitochondrial function before and after the addition of Exendin-4. Based on these observations, we discuss the protective role of Exendin-4 against mitochondrial oxidative damage and its relationship with Ca(2+)-independent phospholipase A2. Methods We established a pancreatic β-cell oxidative stress damage model using Min6 cell lines cultured in vitro with tert-buty1 hydroperoxide and hydrogen peroxide. We then added Exendin-4 to observe changes in the rate of cell apoptosis (Annexin-V-FITC-PI staining flow cytometry and DNA ladder). We detected the activity of the caspase 3 and 8 apoptotic factors, measured the mitochondrial membrane potential losses and reactive oxygen species production levels, and detected the expression of cytochrome c and Smac/DLAMO in the cytosol and mitochondria, mitochondrial Ca2-independent phospholipase A2 and Ca(2+)-independent phospholipase A2 mRNA. Results The time-concentration curve showed that different percentages of apoptosis occurred at different time-concentrations in tert-buty1 hydroperoxide- and hydrogen peroxide-induced Min6 cells. Incubation with 100 µmol/l of Exendin-4 for 48 hours reduced the Min6 cell apoptosis rate (p<0.05). The mitochondrial membrane potential loss and total reactive oxygen species levels decreased (p<0.05), and the release of cytochrome c and Smac/DLAMO from the mitochondria was reduced. The study also showed that Ca(2+)-independent phospholipase A2 activity was positively related to Exendin-4 activity. Conclusion Exendin-4 reduces Min6 cell oxidative damage and the cell apoptosis rate, which may be related to Ca(2)-independent phospholipase A2.